2015
DOI: 10.1037/a0038252
|View full text |Cite
|
Sign up to set email alerts
|

What clinicians want: Findings from a psychotherapy practice research network survey.

Abstract: Practice research networks may be one way of advancing knowledge translation and exchange (KTE) in psychotherapy. In this study, we document this process by first asking clinicians what they want from psychotherapy research. Eighty-two psychotherapists in 10 focus groups identified and discussed psychotherapy research topics relevant to their practices. An analysis of these discussions led to the development of 41 survey items. In an online survey, 1,019 participants, mostly practicing clinicians, rated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 30 publications
3
49
0
11
Order By: Relevance
“…Researchers have found consistent positive associations between therapeutic alliance and therapeutic outcome (Horvarth & Bedi, 2002;Orlinsky, Ronneslad, & Willutzki, 2004). Regardless of the type of therapy or philosophical orientation, therapists have been interested in therapeutic alliance as a vital element of therapeutic outcome (Tasca et al, 2015).…”
Section: Music Therapy Intervention and Therapeutic Alliancementioning
confidence: 99%
“…Researchers have found consistent positive associations between therapeutic alliance and therapeutic outcome (Horvarth & Bedi, 2002;Orlinsky, Ronneslad, & Willutzki, 2004). Regardless of the type of therapy or philosophical orientation, therapists have been interested in therapeutic alliance as a vital element of therapeutic outcome (Tasca et al, 2015).…”
Section: Music Therapy Intervention and Therapeutic Alliancementioning
confidence: 99%
“…Philosophical barriers identified in the literature are typically related to staff perceiving the measures as unimportant, unhelpful, or even antithetical to their values. For example, a survey on the research interests of Canadian clinical psychologists suggested that clinicians had little interest in using outcome monitoring tools or related research to enhance their psychotherapy practice (Tasca et al, 2015). The authors suggest that clinicians may perceive outcome monitoring as an "externally imposed agenda" as opposed to a practice that can enhance clients' treatment outcomes (p. 9; Tasca et al, 2015).…”
Section: Definition Of Key Terms Related To Implementation In Order mentioning
confidence: 99%
“…Goldfried and Wolfe () described the relationship as a “strained alliance”. Tasca () refers to a “practice–research divide, which is widely acknowledged as a problem in psychotherapy” and Henton () has suggested that psychotherapy and research are often characterised as “opposing domains”. An almost dichotomous relationship between psychotherapy practice and research is also identified by Darlington and Scott ().…”
Section: Therapists and Researchmentioning
confidence: 99%